Disentangling motivational and experiential aspects of "Utility": A neuroeconomics perspective - Ulrich Witt; Martin Binder (Max Planck Institute of Economics, 2011)
Although decision makers are often reported to have difficulties in making comparisons between multi-dimensional decision outcomes, economic theory assumes a uni-dimensional utility measure. This paper reviews evidence from behavioral and brain sciences to assess whether, and for what reasons, this assumption may be warranted. It is claimed that the decision makers' difficulties can be explained once the motivational aspects of utility (wanting) are disentangled from the experiential ones (liking) and the features of the different psychological processes involved are recognized.
Keywords: D87; B41; B12; 330; utility; neuroeconomics; index number problem; wanting; liking; affective forecasting; Nutzen; Neuroökonomie; Entscheidung; Motivation; Bedürfnisse; Theorie